Il valore teoretico della fenomenologia “classica” di Edmund Husserl ed Edith Stein e il suo contributo alla fondazione delle scienze umane - Ales Bello, Angela (Bollettino Filosofico, 2018)
The so-called “classical” phenomenology is the position of the founder of the phenomenological movement, Edmund Husserl and of his faithful disciple Edith Stein. Other direct or indirect disciples could also be included but, in my opinion, the most distinctive feature of the classical position is the Husserlian analysis of the human subject as a starting point for the examination of reality. In the first part of my paper I show that such an analysis was already done by the modern philosophers, but Husserl was the one who was able to go to the “thing in itself”. What is at stakes in  the discussion is the meaning of philosophy itself, namely that kind of human research aiming at an understanding of what manifests itself to us and presses us to give an answer. In the second part of my paper, I deal with the application of phenomenological analysis to the field of human sciences, showing that Husserl’s and Stein’s intention was to supply with basic indications on the structure of the human the researchers involved in field such as psychology, psychopathology, sociology and religion.